Hydrogen Adsorption in Nanoporous Nickel(II) Phosphates - Forster, Paul M; Eckert, Juergen; Chang, Jong-San; Park, Sang-Eon; Férey, Gérard; Cheetham, Anthony K (Journal of the American Chemical Society, 2003)
Hydrogen sorption in the nanoporous nickel phosphates VSB-1 and VSB-5 has been studied with a combination of BET, temperature programmed desorption (TPD), and inelastic neutron scattering (INS) measurements. H2 BET isotherms for VSB-1 are similar to those seen in nanoporous zeolites, while VSB-5 adsorbs substantially more hydrogen due to a steep initial uptake at low partial pressures. TPD data show that hydrogen interacts strongly with VSB-5, with desorption peaks at 109 and 149 K in a nitrogen flow, whereas the absence of similar peaks for VSB-1 suggests a weaker interaction. INS spectra of the rotational tunnel transition of the adsorbed H2 also reveal a strong interaction with the VSB-5 host. These data strongly suggest the existence of coordinatively unsaturated Ni2+ sites accessible to H2 molecules in the pores of VSB-5.